Carbon stock estimation of mangrove vegetation using remote sensing in Bacan, Awanggoa District, South Halmahera - Supyan Supyan; Ardan Samman; M. Janib Achmad; Ariyati Fadel; Maskur Abdul Kadir (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Awanggoa Village in Bacan District, South Halmahera Regency, has experienced significant residential expansion, converting around 9 hectares of mangrove land into a residential area. The remaining mangrove ecosystem, covering an area of 16.84 hectares in the northern part of the village, is starting to experience degradation, especially along the coast and southern areas. This condition requires management policies that ensure the sustainability of the ecosystem. The purpose of this research is to analyze the NDVI condition of the mangrove ecosystem, as well as measure biomass, carbon stock, and CO2 absorption, using remote sensing methods via the GEE application (https://code.earthengine.google.com) with data collected from January 1 to December 31, 2023. The research results show a total biomass of 101.21 tons ha, carbon stock of 47.57 tons C ha, and CO2 storage of 174.88 tons C. Dense vegetation is very important for carbon storage and emission reduction, thus supporting sustainable mangrove ecosystem management and environmental conservation efforts.